2018 Academic Emergency Medicine Consensus Conference: A Workforce Development Research Agenda for Pediatric Care in the Emergency Department. (20th November 2018) - Merritt, Chris; Dietrich, Ann M.; Bogie, Amanda L.; Wu, Fred; Khanna, Kajal; Ballasiotes, Mary Kay; Gerardi, Michael; Ishimine, Paul T.; Denninghoff, Kurt R.; Saidinejad, Mohsen
Abstract: Each year, more than 30 million children visit U.S. emergency departments (EDs). Although the number of pediatric emergency medicine specialists continues to rise, the vast majority of children are cared for in general EDs outside of children's hospitals. The diverse workforce of care providers for children must possess the knowledge, experience, skills, and systemic support necessary to deliver excellent pediatric emergency care. There is a crucial need to understand the factors that drive the professional development and support systems of this diverse workforce. Through the iterative process culminating with the 2018 Academic Emergency Medicine consensus conference, we have identified five key research themes and prioritized a specific research agenda. These themes represent critical gaps in our understanding of the development and maintenance of the pediatric emergency care workforce and allow for a prioritization of future research efforts. Only by more fully understanding the gaps in workforce needs, and the necessary steps to address these gaps, can outcomes be optimized for children in need of emergency care.